Two New Compounds from Alcea rosea - Cheng, Weiming; Cheng, Xiaqian; Liu, Zhijun; Zeng, Yongchi (Asian Journal of Chemistry, 2012)
Five compounds had been isolated and purified from Alcea rosea, among which two were new compounds. The structure of the two new compounds were elucidated and characterized as 1'-hydroxy-3'-formyl-4-methylol-5-(4''-O-b-D-glucoside-3''-methoxyphenyl)-benzofuran and 1-(2'-methoxy-4'-hydroxy-5'-acetylphenyl)-3-methylbutan-1-one and named as Rosea A and Rosea B, respectively.